PENDEKATAN PENEMUAN TERBIMBING PENGEMBANGAN DARI BAHAN AJAR KALKULUS BERORIENTASI NILAI KEISLAMAN DAN BERWAWASAN LINGKUNGAN - fitria selvera nanda (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2020)
The aims of this research include: 1) Knowing how to develop Islamic value-oriented teaching materials and environmentally sound using guided inventions. 2) Knowing the feasibility of the value-oriented Islamic and environmentally sound. 3) know the effectiveness of learning materials that are value-oriented and environmentally sound in learning with findings. The type of research used is by the Research and Development method. The research uses the ADDIE research model. This research instrument is a validation sheet of the teaching materials developed using an ADDIE model consisting of analysis, design, development, implementation and evaluation stage. The results of this study are calculus teaching materials on the derivative materials of Islamic values and environmental insight with guided discovery approaches developed into valid/feasible categories, while the results of the analysis of the effectiveness of class data applied learning using calculus teaching materials on the derivatives of value-oriented material and environmental insight with a guided discovery approach is effective with the average N-Gain (g) ≥ 0.77/high category.